Influence of Post-Disaster Housing Reconstruction on Community Stability in Ahoada East Local Government Area, Rivers State, Nigeria (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study examined the influence of post-disaster housing reconstruction on community stability in Ahoada East Local Government Area, Rivers State, Nigeria. The area is frequently affected by flooding that disrupts housing, livelihoods, and social order. The study focused on three reconstruction dimensions: damage and needs assessment, emergency shelter provision, and construction and rehabilitation strategies. A descriptive survey research design was adopted. The population comprised 1,240 residents of flood-affected communities. A sample of 300 respondents was selected using simple random sampling. Data were collected using a structured questionnaire titled Post-Disaster Housing Reconstruction and Community Stability Questionnaire (PDHRCSQ). Data were analyzed using mean, standard deviation, and simple linear regression at 0.05 significance level. Findings revealed that damage and needs assessment significantly influenced community stability (R²=0.38). Emergency shelter provision also had a significant influence (R²=0.44). Construction and rehabilitation strategies showed the strongest influence (R²=0.50). The study further showed that all variables had positive and significant relationships with community stability. It was concluded that effective housing reconstruction enhances recovery, reduces displacement, and strengthens social cohesion. The study recommends improved assessment systems, coordinated shelter provision, and enforcement of resilient construction standards. The findings underscore the importance of integrating disaster risk reduction into housing reconstruction policies in flood-prone communities such as Ahoada East. This approach will enhance resilience and ensure sustainable community development after flooding events in the study area. Consequently, policymakers and disaster management agencies should prioritize integrated reconstruction frameworks to strengthen long-term stability and reduce future disaster vulnerability in the region and resilience outcomes